Generational differences in values and patterns of thinking in the workplace - Kwiecińska, Monika; Grzesik, Katarzyna; Siewierska-Chmaj, Anna; Popielska-Borys, Anna (Publishing House of Wroclaw University of Economics and Business, 2023)
The aim of this article is to empirically identify and analyse the differences between generations X, Y and Z in terms of values and patterns of thinking in the workplace. For the purposes of achieving the set objective, quantitative studies were performed. Data were obtained with the use of the MindSonar psychometric test. The results were subjected to a statistical analysis, and 435 economically active respondents took part in the study. The study shows that there are numerous statistically significant differences in preferred values and patterns of thinking among representatives of various generations (the differences occur in 2 out of the 7 measured levels of existence and their corresponding values, and in 9 out of the 32 measured patterns of thinking, or metaprograms). The obtained results may help HR managers and specialists focus on real, diagnosed differences in employees, which may be used for determining and communicating organisational priorities for current and future employees.
Argumenta Oeconomica, 2023, Nr 1 (50), s. 95-118
Keywords: generations; values; patterns of thinking; workplace; Poland